2009
DOI: 10.1123/ssj.26.2.191
|View full text |Cite
|
Sign up to set email alerts
|

Medical Uncertainty and Clinician–Athlete Relations: The Management of Concussion Injuries in Rugby Union

Abstract: Concussion Injuries in Rugby UnionThis paper addresses clinical practice in sport medicine. Combining notions of medical uncertainty with a figurational sociological emphasis on interdependence, the paper illustrates how uncertainty characterizes the medical understanding, clinical treatment, and patient experience of concussion. Faced with uncertainty, the clinician's desire for recognition and validation through athletes' dependence on them enables medically-based diagnostic and treatment guidelines to be re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0
6

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(73 citation statements)
references
References 35 publications
1
66
0
6
Order By: Relevance
“…Waddington and Roderick reported how a physiotherapist falsified information in order to protect a footballer with an alcohol problem [12], while Anderson [37] relayed clinicians' stories of creating fictitious physical injuries to obscure athletes' mental health issues. These reports mirror findings regarding clinicians' avoidance of concussion diagnoses in order to obviate conflict with athletes and coaches (39). Conversely, in an alarming case of alleged malpractice, a footballer recalled a doctor threatening to release confidential medical information (which turned out to be false) in order to dissuade the player from seeking a lucrative transfer [12].…”
Section: Operationalizing Patient Confidentiality In Sportmentioning
confidence: 71%
“…Waddington and Roderick reported how a physiotherapist falsified information in order to protect a footballer with an alcohol problem [12], while Anderson [37] relayed clinicians' stories of creating fictitious physical injuries to obscure athletes' mental health issues. These reports mirror findings regarding clinicians' avoidance of concussion diagnoses in order to obviate conflict with athletes and coaches (39). Conversely, in an alarming case of alleged malpractice, a footballer recalled a doctor threatening to release confidential medical information (which turned out to be false) in order to dissuade the player from seeking a lucrative transfer [12].…”
Section: Operationalizing Patient Confidentiality In Sportmentioning
confidence: 71%
“…As with previous research (Malcolm, 2009) The player went down like he'd been knocked unconscious so I'm there within seconds.…”
Section: Exploring the Social Construction Of Medical Beliefsmentioning
confidence: 79%
“…Sports psychologists, in demonstrating the long-term psychological impacts such as anxiety, depression, social withdrawal, loss of identity and suicidal ideation, have been critical of the dominance of medicine's tendency to reduce neurocognitive outcomes through quantitative methodologies (Caron et al, 2013) To date sociologists of sport have provided just two studies of the lived experience of SRC. Malcolm (2009) initially drew on figurational sociology and concepts of medical uncertainty to explain how and why this sporting community sometimes circumvented, and sometimes openly rejected, relatively precautionary SRC policy initiatives. He further concluded that the unintended consequences of rules designed to protect players' health could lead clinicians to replace textbook diagnostic criteria with more subjective understandings of concussion, "that they know will be acceptable to others" (Malcolm, 2009, p. 201).…”
Section: Social Scientific Responses To the Src Agendamentioning
confidence: 99%
“…Athletes show pronounced levels of negotiation over treatment, a propensity to question the expertise of clinicians (Thing, 2012), and/or a tendency to simply avoid consultation outright (Malcolm, 2009). While some practices appear to be specific to the particular context/sport, British and North American sport have largely produced similar results, and the differences identified between male and female experiences of pain and injury in sport appear minimal (Young & White, 1993).…”
Section: Sport Pain and Injurymentioning
confidence: 99%
“…We could explore further the importance of trust (Mechanic & Meyer 2000) in the patient-clinician relationship and the importance of practice context for patient experience and clinician control. We could explore in more detail the experiences of particular conditions, distinguishing between patients' experiences of acute and chronic conditions (we have largely only investigated chronic conditions to date), and 'invisible' injuries such as concussion (Malcolm, 2009) and asthma (Allen-Collinson & Owton 2012) with not only visible but sometimes highly public conditions such as broken bones. By conceptualizing illness more broadly, we could explore experiences of asymptomatic populations exposed to the 'policing' function of sports medicine.…”
Section: Defining a Research Agenda For The Sociology Of Sport Healtmentioning
confidence: 99%